A First Phylogeny of the Genus Dimocarpus and Suggestions for Revision of Some Taxa Based on Molecular and Morphological Evidence - Suparat K. Lithanatudom (2018)
© 2017 The Author(s). Dimocarpus longan, commonly known as the longan, belongs to the family Sapindaceae, and is one of the most economically important fruits commonly cultivated in several regions in Asia. There are various cultivars of longan throughout the Thai-Malay peninsula region, but until now no phylogenetic analysis has been undertaken to determine the genetic relatedness of these cultivars. To address this issue, 6 loci, namely ITS2, matK, rbcL, trnH-psbA, trnL-I and trnL-trnF were amplified and sequenced from 40 individuals consisting of 26 longan cultivars 2 types of lychee and 8 herbarium samples. The sequencing results were used to construct a phylogenetic tree using the neighbor-joining (NJ), maximum likelihood (ML) and Bayesian inference (BI) criteria. The tree showed cryptic groups of D. longan from the Thailand-Malaysia region (Dimocarpus longan spp.). This is the first report of the genetic relationship of Dimocarpus based on multi-locus molecular markers and morphological characteristics. Multiple sequence alignments, phylogenetic trees and species delimitation support that Dimocarpus longan spp. longan var. obtusus and Dimocarpus longan spp. malesianus var. malesianus should be placed into a higher order and are two additional species in the genus Dimocarpus. Therefore these two species require nomenclatural changes as Dimocarpus malesianus and Dimocarpus obtusus, respectively.